Life course health development of individuals with neurodevelopmental conditions. (23rd February 2017) - Palisano, Robert J; Di Rezze, Briano; Stewart, Debra; Rosenbaum, Peter L; Hlyva, Oksana; Freeman, Matthew; Nguyen, Tram; Gorter, Jan Willem
Abstract : The life course health development (LCHD) model by Halfon et al. conceptualizes health development occurring through person–environment transactions that enable well‐being and participation in desired social roles throughout life, areas that have not received adequate attention in healthcare. The aim of this 'perspectives' paper is to apply the six core tenets of the LCHD model and the concept of health development trajectories to individuals with lifelong neurodevelopmental conditions. We share the perspective that modifiable aspects of the environment often restrict health development; we then advocate that children, beginning at a young age, should engage in 'real‐world' experiences that prepare them for current and future social roles. LCHD encourages future planning from the outset, continuity of care between pediatric and adult systems, and coordination of services and supports. We believe LCHD can be transformative in enabling healthy living of individuals with neurodevelopmental conditions. What this paper adds: Health development in neurodevelopment conditions occurs through person–environment transactions. Timing and social structuring determine whether participation positively or negatively influences health development.